Inner Ear Anomalies in Children With Apert Syndrome: A Radiological and Audiological Analysis. Issue 5 (10th July 2022) - Hogg, Emma S.; Turgut, Nesrettin F.; McCann, Emma; Avula, Shivaram; De, Sujata; Sharma, Sunil D.
Abstract : Introduction: Apert syndrome is a multisystem genetic disorder typically characterized by craniosynostosis and syndactyly. Studies also report an increased incidence of hearing loss in children with Apert syndrome in comparison to the general population. The aim of this study was to gain an understanding of the inner ear radiological anatomical variations seen in children with Apert syndrome and correlate these with audiological outcomes. Materials and Methods: This was a retrospective review of computed tomography imaging of patients with Apert syndrome. Radiological images were examined for anatomical variations in inner ear structures. These were correlated with audiological testing. Results: Nineteen patients were included in the study. The most commonly observed anomaly was an absent bony window of the lateral semi-circular canal (SCC) in 11 patients (58%), followed by an enlarged lateral SCC in 12 patients (63%). This combination of anomalies was seen collectively in 42% of patients and together these give the appearance of a 'rectangular vestibular cavity'. Audiological results were available in 11 patients and 9 of these patients had a conductive hearing loss. Conclusion: To the authors' knowledge, this is the first study that reports radiological findings alongside audiological testing in Apert syndrome and describes the appearance of a 'rectangular vestibular cavity'.